MERANCANG KOMUNITAS ANAK MUDA BERBASIS ARSITEKTUR EKOLOGI - Estefany Betzy Gultom; Mieke Choandi (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
During the pandemic, student activities do not take place optimally. Whether in the social activities or formal learning, everything must be limited following government regulations. And these days, where humans use natural resources irregularly and do city development that exploits the ecosystem. When we are doing a development. We should pay more attention and efforts to maintain natural ecosystems, because natural resources are not only for the current generation but for the needs of younger generation in the future. The city of Bogor itself has a lot of potential both in the social and ecological fields. Bogor weather climate is very good where the city itself is famous in terms of agriculture and plantations. The majority of residents in the city of Bogor are on a productive age. Facilities for adolesence itself are already available, but the programs that offered are more directed to non-academic activities. Therefore this building is designed to accommodate the needs of young people ranging from non-academic needs to the needs of non-formal education. With the programs that offered, which aim to improve the social and economic quality of young people in the city of Bogor. Ecological Architecture method are used in this building. It is applied to the program and maintenance building systems, which refers to the 6 Beyond Ecology Principals. The use of a symbiotic theme is applied to the building program and also the building maintenance system, which aims to save energy. Key Words: Ecology; Ecology Architecture; Youth Centre AbstrakPada masa pandemi kegiatan belajar-mengajar tidak berlangsung secara maksimal. Baik dalam kegiatan sosial atau pembelajaran formal, semuanya harus dibatasi mengikuti peraturan pemerintah. Dan di era globalisasi seperti sekarang ini dimana manusia memanfaatkan sumber daya alam dengan tidak teratur dan melakukan banyak pembangunan yang mengeksploitasi ekosistem. Pembangunan seharusnya lebih memperhatikan upaya untuk menjaga ekosistem alam karena sumber daya alam tidak hanya untuk generasi sekarang namun untuk kebutuhan generasi muda di masa depan. Kota Bogor sendiri memiliki banyak potensi baik di bidang sosial maupun ekologinya. Iklim kota Bogor sangat bagus dimana kotanya sendiri terkenal dalam hal pertanian dan perkebunan. Penghuni kota Bogor mayoritas adalah penduduk di usia produktif. Fasilitas anak muda di kota Bogor sendiri sudah tersedia namun program yang ditawarkan lebih mengarah ke kegiatan non akademik. Sehingga bangunan dirancang untuk mewadahi kebutuhan anak muda mulai dari kebutuhan non-akademik sampai ke kebutuhan pendidikan non-formal. Dengan program-program yang ditawarkan, yang bertujuan untuk meningkatkan kualitas sosial dan ekonomi anak muda di Kota Bogor. Penerapan  metode Arsitektur Ekologi dalam merancang fasilitas untuk anak muda di Kota Bogor diaplikasikan pada program dan sistem perawatan dalam bangunan, yang mengacu terhadap 6 Beyond Ecology Principal. Pengunaan tema simbiosis yang diaplikasikan pada program bangunan dan juga sistem perawatan bangunannya, yang bertujuan untuk menghemat energi.